Colorimetric enzymatic assay of L-malic acid using dehydrogenase from baker's yeast - Peres, Maristela F.S. [UNESP] (2008)
A colorimetric method has been developed and optimized to measure L-malic acid in samples of fruit juices and wine. This method is based on oxidation of the analyte, catalyzed by malate dehydrogenase (MDH) from dry baker's yeast, and in combination with the reduction of a tetrazolium salt (MTT: 3-(4,5-dimethylthiazol-2-y1)-2,5-diphenyrtetrazolium bromide). In the present study, the method exhibited sensitivity in the range of 500-4000 μM of L-malic acid in the reaction cuvette, with the lower detection limit of 6.7.10-2 g/L, the upper limit of 53.6.102 g/L and a maximum standard deviation of only 2.5 % for the analyzed samples. The MDH activity from baker's yeast was also optimized, the enzyme showed a high stability at pH=8.0-9.0 and the activity was maintained completely at temperatures up to 40 °C for 1 hour. The results show that the colorimetric method using enzymatic preparations from dry baker's yeast is a simple and low-cost method with possibility of wide application.